Implementasi Metode Al Ikhtishor Dalam Pembelajaran Nahwu Di Ponpes Durrotu Ahlissunnah Waljama’ah Semarang - Sulaiman, Agus; Munirul Abidin (Penerbit Minhaj Pustaka, 2024)
This study aims to evaluate the level of learning nahwu, measure the ability of students in nahwu, and assess the effectiveness of using the Al Ikhtishor method in nahwu learning at Durrotu Ahlissunnah Waljama'ah Islamic Boarding School. This research uses quantitative methods with experimental design, involving control classes and experimental classes. Data collection techniques include tests, interviews, and documentation. Data analysis was carried out through normality tests, homogeneity tests, and T tests (Paired Sample T Test and Independent Sample T-Test ). The results showed that the level of use of the Al Ikhtishor method was adequate, the ability of students in learning nahwu science was very good, and the use of the Al Ikhtishor method proved effective in increasing understanding and mastery of nahwu among students. The Al Ikhtishor method significantly increases the understanding and mastery of nahwu among students. The conclusion of this study is that the Al Ikhtishor method is effective in improving the quality of nahwu learning, and this method is recommended for use in teaching nahwu science in Islamic boarding schools.